2018
DOI: 10.1002/slct.201801453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimycobacterial Evaluation of Piperazyl‐alkyl‐Ether Linked 7‐Chloroquinoline‐Chalcone/Ferrocenyl Chalcone Conjugates

Abstract: A series of piperazyl‐alkyl‐ether linked 7‐chloroquinoline‐chalcone/ferrocenyl chalcone conjugates were synthesized and evaluated for their anti‐mycobacterial activities against the mc26230 strain of Mycobacterium tuberculosis and cytotoxicity against the Vero cell line. While all the compounds showed limited cytotoxicity, the ferrocenyl‐chalcone conjugate with pentyl chain as spacer proved to be most potent among the series with a Minimum Inhibitory Concentration (MIC) of 14 μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, all compounds were less active and more toxic than the standards (Quinine and Camptothecin) (Ansari et al, 2017). However, Singh et al proved that the introduction of ferrocene ring improved the antitubercular activities in general with conjugate 49 exhibiting MIC of 14 μg/ml comparable to the most active conjugate 50 in the series which does not have ferrocene ring MIC of 15 μg/ml (Singh, Viljoen, Kremer, & Kumar, 2018). In 2018, Shalini et al identified compound 51 against M. tuberculosis , it exhibited activity (MIC 50 : 2.2 μg/ml) against mc26230 strain.…”
Section: Pharmacological and Biological Activitiesmentioning
confidence: 99%
“…However, all compounds were less active and more toxic than the standards (Quinine and Camptothecin) (Ansari et al, 2017). However, Singh et al proved that the introduction of ferrocene ring improved the antitubercular activities in general with conjugate 49 exhibiting MIC of 14 μg/ml comparable to the most active conjugate 50 in the series which does not have ferrocene ring MIC of 15 μg/ml (Singh, Viljoen, Kremer, & Kumar, 2018). In 2018, Shalini et al identified compound 51 against M. tuberculosis , it exhibited activity (MIC 50 : 2.2 μg/ml) against mc26230 strain.…”
Section: Pharmacological and Biological Activitiesmentioning
confidence: 99%
“…[3] Further studies on benzodiazepines led to the conclusion that they exhibited good anti-cancer [4,5] , antibacterial [6] , antifungal [7] , anti-inflammatory [8,9] , antitubercular [10] , and anticonvulsant properties [11,12] Chalcone, a biologically active compound was extracted naturally from plants and was used for the formation of many flavonoids and isoflavonoids heterocycles. [13][14][15][16] Chalcone being a biologically active compound itself reported many properties like antibacterial 17] , antioxidant [18] , antimycobacterial [19] , antitumor [20] , antituberculosis [14] , and cytotoxicity [21] . Apart from this, they are also used to synthesise many heterocycles such as benzodiazepines [22] , pyrazolines [23,24] , isoxazoles [25] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones are considered as vital intermediates to synthesize wide variety of heterocyclic compounds with broad-spectrum of biological activities. [11][12][13][14][15][16] The extraordinary pharmacological profile of chalcones and their hybrid derivatives include anticancer, [17][18][19][20] anti-tubercular, 21,22 antibacterial, [23][24][25][26] anti-HIV, [27][28][29][30] antimalarial, [31][32][33][34] antioxidants, [35][36][37] antiviral, [38][39][40] antifungal, [41][42][43][44][45] cardiovascular, 46,47 antitumor, [48][49][50] antiulcer, 51 anticonvulsant, 52,53 anti-inflammatory, [54][55][56][57][58]…”
Section: Introductionmentioning
confidence: 99%